INFLUENCE OF SOIL CULTIVATION METHOD ON THE INTENSITY OF CESIUM-137 ACCUMULATION IN THE VEGETATIVE MASS OF DACTYLIS GLOMERATA (DACTYLIS GLOMERATA L.) - Didur І.; Alieksieiev О.; Lototskyi Р.; Balkovskyi О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Technogenic activities have led to the contamination of various environmental components, including natural meadows, with various toxic substances. Given the limited effectiveness of agrotechnological measures to improve these natural meadows, they are among the most critical areas for producing high-quality and safe plant raw materials. Natural meadows endured significant technogenic stress due to the Chornobyl nuclear power plant accident, resulting in contamination with radionuclides, notably cesium-137, which is particularly dangerous due to its high mobility in the soil-plant system. This article presents research findings on the impact of different soil tillage methods on natural meadows, 38 years after the Chornobyl accident, specifically regarding the accumulation of cesium-137 in the vegetative mass of Dactylis glomerata. The study was conducted in the Right-Bank Forest-Steppe of Vinnytsia region, on gray forest soils of natural meadows that had not been cultivated during this period. Two research variants were implemented, each with four repetitions, using 25 m² plots. The first variant involved disking the soil to a depth of 10-14 cm, while the second involved plowing to a depth of 22-24 cm. Both processes were performed in the autumn. Before sowing the grasses in the spring, pre-sowing cultivation and harrowing were carried out. Soil samples for radiological analysis were collected using the envelope method from five points, with each sample weighing 0.5 kg, and taken from a depth of 10 cm. The vegetative mass of Dactylis glomerata was collected through spot sampling from an area of 1 m² for each research variant and its repetitions, before the beginning of the budding phase. The content of cesium-137 in both the soil and the vegetative mass of Dactylis glomerata was measured using a SEG-05 gamma spectrometer. The findings revealed that disking the natural meadows to a depth of 14 cm reduced the cesium-137 content in the 10-cm soil layer by 5.6%, while plowing to a depth of 24 cm decreased it by 2.07 times. Soil treatment of the natural meadows positively impacted the reduction of cesium-137 accumulation in the vegetative mass of Dactylis glomerata. Disking to a depth of 14 cm reduced the cesium-137 content in the vegetative mass by 11.0% while plowing to a depth of 24 cm reduced it by 44.1%. These results underscore the significance of agronomic practices for enhancing the quality of plant raw materials in contaminated land conditions.